(untitled) (KYAMC Journal, 2020)
Since its’ introduction in 2017, Distal Transradial Access (dTRA) has shown it’s advantages over conventional Transradial Approach in terms of risk with Radial Artery Occlusion (RAO) and with the comfort level for both the patient and operator. A large number of patients requiring subsequent intervention gets much benefit with this new technique of Radial Artery (RA) preservation, as it is a refinement of the conventional approach. On the other hand, the most challenging part it has is the supreme level of expertise for a successful puncture for the advancement with the procedure. Still, this new technique has been obtained by the Interventionists world wide with the simultaneous study on it to make the distal transradial access as a default access site for routine Coronary Angiography (CAG) and Percutaneous Coronary Intervention (PCI). For evaluation with the real world feasibility and safety along with the comfort for both the operator and patient, this study has been conducted. KYAMC Journal Vol. 11, No.-3, October 2020, Page 154-157